Balance of Payments Manual, Sixth Edition Compilation Guide - Valdivia-Velarde, Eduardo (Manuals and Guides, 2016)
The Balance of Payments and International Investment Position Compilation Guide is a companion document to the sixth edition of the Balance of Payments and International Investment Position Manual (BPM6) published in 2009. The purpose of the Guide is to show how the conceptual framework described in the BPM6 may be implemented in practice. The Guide is not intended to be a 'stand-alone' manual; users of the Guide should be familiar with the BPM6.